2014
DOI: 10.1080/00028487.2014.969407
|View full text |Cite
|
Sign up to set email alerts
|

Coastwide Otolith Signatures of Juvenile Atlantic Menhaden, 2009–2011

Abstract: The Atlantic Menhaden Brevoortia tyrannus is a clupeid that plays a critical role in the marine food web and supports one of the largest fisheries on the U.S. East Coast. Along with a decrease in overall numbers and spawning stock biomass, recruitment levels have remained low since the 1990s. Atlantic Menhaden use numerous estuaries along the Atlantic coast for juvenile development before recruiting to the adult population, but the contribution of each of these nursery grounds is currently unknown. Chesapeake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
(73 reference statements)
3
13
0
Order By: Relevance
“…Otolith chemistry is one of the most widely used methods. Provided that water chemistry is reflected in the chemistry of the otolith layer being deposited and remains unchanged with fish growth (Campana, ), the rationale for estimating adult natal origin is to compare the microchemistry of the inner part of the adult otolith with those of juveniles from all putative sources (Elsdon et al ., ; Anstead et al ., ). This, however, is often a challenging task (Catalan et al ., ; Morales‐Nin et al ., ) and, among other technical problems, scientists face the dilemma of which classification methods for assignment to choose.…”
Section: Introductionmentioning
confidence: 97%
“…Otolith chemistry is one of the most widely used methods. Provided that water chemistry is reflected in the chemistry of the otolith layer being deposited and remains unchanged with fish growth (Campana, ), the rationale for estimating adult natal origin is to compare the microchemistry of the inner part of the adult otolith with those of juveniles from all putative sources (Elsdon et al ., ; Anstead et al ., ). This, however, is often a challenging task (Catalan et al ., ; Morales‐Nin et al ., ) and, among other technical problems, scientists face the dilemma of which classification methods for assignment to choose.…”
Section: Introductionmentioning
confidence: 97%
“…Proceeding with four clusters in the adult data based on previous studies (Ahrenholz et al 1989;ASMFC 2004;Anstead et al 2015Anstead et al , 2016 and supported by the small pseudo t 2 statistics and large pseudo F statistic, we assigned adults of unknown origin to their nursery ground using the QDA. We found that, on average, 40% of age-2 Atlantic Menhaden originated in the northeastern nursery region, 8% in Delaware Bay, 22% in Chesapeake Bay, and 30% in the southeastern region for the 2008-2010 yearclasses (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Juvenile Atlantic Menhaden were collected in 2009-2011 from multiple sites along the U.S. Atlantic coast, prepared, and analyzed as described in Anstead et al (2015). Adult Atlantic Menhaden (ages 2 and older) were collected in 2010-2012 from the coastal waters from Cape Cod to the Hudson River, Delaware Bay, Chesapeake Bay, Pamlico Sound, and Charleston Sound ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations